Problematika Tentang Penyediaan Pembuatan Tanda Nomor Kendaraan Bermotor Tidak Resmi di Daerah Balikpapan dan Akibat Hukum - Novita Sari (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACTNovita Sari, Law Studies Program, Faculty of Law, University of 17 August 1945 "Problems on the Making of Illegal Vehicle’s number in Balikpapan Area and Because of Law", under the guidance of Kunti Widayati SH, M.Hum as the advisor I and Isnawati, SH , HM as advisor II.In this research that became the object of this research is the Balikpapan City District Police Traffic and Office of Samsat Balikpapan City and Business maker of Illegal Vehicle’s number and also the users of illegal Vehicle’s number. This research was conducted in Balikpapan City with Empirical Research method, using Law Case Study Approach which is case study approach on legal affair which is in progress or not finished. Source of data obtained in this research is primary data source or secondary data related to the making of illegal vehicle’s number.Vehicle’s number is an integral part of the registration and identification of vehicles, which basically Vehicle’s number can only be issued by the police in this case is the Indonesian Traffic Police Corps, but in fact there are still many business actors open a business providing Vehicle’s number that is clearly not justifiable legally. The result of the research and discussion related to the cause of the illegal construction of Vehicle’s number due to the absence of clear rules for action against illegal Vehicle’s number production so that law enforcers have no basis to carry out the action, the number of requests for business maker of illegal Vehicle’s number caused by the long process of making Vehicle’s number in Samsat Office, and the development of the illegal Vehicle’s number making business is quite fast in Balikpapan City Region. The concept offered by the author in this case is to optimize the supervision on the provision of making the illegal Vehicle’s number, clarify the rules regarding the making of Vehicle’s number not through  Samsat office, so that in law enforcement can be carried out fairly and useful in accordance with the purpose of the law itself. Keywords: Causative factor, Law Enforcement, Illegal Vehicle’s number.